2005
DOI: 10.1094/php-2005-0107-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Azoxystrobin, Pyraclostrobin, Potassium Phosphite, and Mefenoxam for Control of Strawberry Leather Rot Caused by Phytophthora cactorum

Abstract: Efficacy of azoxystrobin, pyraclostrobin, mefenoxam, and potassium phosphite for control of strawberry leather rot, caused by Phytophthora cactorum, was evaluated on a commercial farm. Foliar sprays of azoxystrobin, pyraclostrobin, and potassium phosphite were applied weekly from bloom through harvest and mefenoxam was applied twice as a soil drench at early plant growth and at fruit set. All fungicide treatments had significantly less leather rot than the untreated control and there were no significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
0
14
0
2
Order By: Relevance
“…All of these fungicides provide effective control of leather rot (28). In addition, the QoI (strobilurin) fungicides azoxystrobin and pyraclostrobin provide excellent activity against leather rot under very high disease pressure in the field (28). The efficacy of these QoI fungicides in field trials was similar to mefenoxam and phosphite fungicides (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All of these fungicides provide effective control of leather rot (28). In addition, the QoI (strobilurin) fungicides azoxystrobin and pyraclostrobin provide excellent activity against leather rot under very high disease pressure in the field (28). The efficacy of these QoI fungicides in field trials was similar to mefenoxam and phosphite fungicides (28).…”
mentioning
confidence: 99%
“…Currently, mefenoxam, fosetyl-Al, and several phosphite fungicides are registered for control of leather rot in the United States. All of these fungicides provide effective control of leather rot (28). In addition, the QoI (strobilurin) fungicides azoxystrobin and pyraclostrobin provide excellent activity against leather rot under very high disease pressure in the field (28).…”
mentioning
confidence: 99%
“…No significant differences were detected among the fungicides treatments. Disease incidences ranged from 0.3 to 0.5% with the QoI fungicides (azoxystrobin and pyraclostrobin), 0.8 to 5.4% with potassium phosphite, and 0.3 to 11% with mefenoxam (Rebollar-Alviter et al 2005). Interestingly, these experiments showed that both QoI fungicides tested were highly effective for control of leather rot of strawberry.…”
Section: Case Study 2: Leather Rot Of Strawberrymentioning
confidence: 90%
“…In order to select the proper fungicide, the efficacy of fungicides was defined in the field (Rebollar-Alviter et al 2005). During 2003 and 2004, the efficacy of pyraclostrobin, azoxystrobin, potassium phosphite and mefenoxam was evaluated in Wooster Ohio, USA against leather rot of strawberry grown in a matted row system.…”
Section: Case Study 2: Leather Rot Of Strawberrymentioning
confidence: 99%
“…El mefenoxam es un fungicida de reciente introducción al mercado español, y su eficacia viene precedida por diversos estudios sobre enfermedades radiculares (Tsor et al, 2005;Stiles, et al, 2005); y sobre las partes aéreas de la planta por oomicetos patógenos (Rebollar-Alviter, 2005 Bajo condiciones controladas en invernadero, todos los tratamientos mostraron porcentajes de control superiores al 50 %, con promedios de área de lesión bastante bajos. Esto podría deberse al menor tamaño de las plantas, lo cual suele maximizar la eficacia de determinados compuestos.…”
Section: Discussionunclassified